2021
DOI: 10.1136/bmjopen-2021-050409
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in Latin America and the Caribbean: a systematic review and meta-analysis

Abstract: ObjectiveTo estimate the pooled prevalence of multimorbidity (≥2 non-communicable diseases in the same individual) among adults of the general population of Latin American and the Caribbean (LAC).DesignSystematic review and meta-analysis.Data sourcesMEDLINE, Embase, Global Health, Scopus and LILACS up to 1 July 2020.Eligibility criteria for selecting studiesThe outcome was the prevalence of multimorbidity. Reports were selected whether they enrolled adult individuals (age ≥18 years) from the general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(40 reference statements)
4
14
2
Order By: Relevance
“…The prevalences found alert to the extent of multimorbidity in Brazil, which may be close to high-income countries with longer life expectancies, such as Portugal [ 42 ], Finland, Spain, and Poland [ 8 ]. Meanwhile, our prevalence was higher than those reported in analyses of the overall population of Latin America and the Caribbean, regarding both combined prevalence (43%; CI: 35%-51%) and combined prevalence excluding Brazilian studies (35%; CI: 26%-43%) [ 43 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The prevalences found alert to the extent of multimorbidity in Brazil, which may be close to high-income countries with longer life expectancies, such as Portugal [ 42 ], Finland, Spain, and Poland [ 8 ]. Meanwhile, our prevalence was higher than those reported in analyses of the overall population of Latin America and the Caribbean, regarding both combined prevalence (43%; CI: 35%-51%) and combined prevalence excluding Brazilian studies (35%; CI: 26%-43%) [ 43 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Globally, about one-third of adults 64 , including a substantial proportion in LMICs [65][66][67] , and more than half of all adults with any chronic condition 19 have multimorbidity 25 . Systematic reviews focusing on community-based studies in both high-income countries (HICs) and LMICs have found a prevalence of 15-43% 28,64,68,69 . A scoping review in LMICs found a prevalence of 3% to 68% in adults, with most of the evidence from Brazil, China, South Africa, India, Mexico and Iran 70 , and 43% in adults in Latin America and the Caribbean 68 .…”
Section: Prevalencementioning
confidence: 99%
“…Systematic reviews focusing on community-based studies in both high-income countries (HICs) and LMICs have found a prevalence of 15-43% 28,64,68,69 . A scoping review in LMICs found a prevalence of 3% to 68% in adults, with most of the evidence from Brazil, China, South Africa, India, Mexico and Iran 70 , and 43% in adults in Latin America and the Caribbean 68 . Prevalence estimates are generally lower in LMICs than in HICs (Fig.…”
Section: Prevalencementioning
confidence: 99%
“…According to the reviews of Abebe et al the prevalence of multimorbidity in LMICs has increased from 3.2 to 67.8% among people over 18 years old (8). Metaanalyses have shown a 43% of prevalence of multimorbidity of chronic conditions in Latin America and the Caribbean (9,10). Yao et al have shown that multimorbidity occurred in 42.4% of the participants aged at least 50 years in China in 2011-2015 (11).…”
Section: Introductionmentioning
confidence: 99%